Biofilm formation in cutaneous wounds and its behavior in the face of interventions: an integrative review - Eline Lima Borges; Josimare Aparecida Otoni Spira; Gilmara Lopes Amorim; Ana Carolina Silva Martins Coelho (Rev Rene, 2022)
Objective: to identify in the literature the biofilm formation and its behavior when faced with interventions in cutaneous wounds. Methods: an integrative review, carried out in the Cumulative Index to Nursing and Allied Health Literature, Latin American and Caribbean Health Sciences Literature, EMBASE, Scopus, The Cochrane Library Collaboration, MEDLINE/PubMed and Science Direct databases, without temporal delimitation. Nineteen studies were selected. The information was evaluated descriptively, comparing it with the pertinent findings. Results: the sample studies were published in English and included three types of biofilm research: two clinical, six in vitro and 11 in vivo (animal). Three themes were included: biofilm model creation (n=4), biofilm assessment (n=3), biofilm behavior before interventions for its management (n=12). Conclusion: the detrimental effects of biofilm on wound healing have been confirmed. Several interventions were able to reduce and eliminate biofilm in in vitro and in vivo models. Contributions to practice: it was found that clinical evaluation of the lesion does not allow the identification of biofilm, even when present; it is below the surface of the lesion. This finding raises reflection on the part of nurses regarding the interventions adopted for the removal of biofilm.